2013
DOI: 10.1007/978-1-4614-7783-9_10
|View full text |Cite
|
Sign up to set email alerts
|

Sperm Selection: Effect on Sperm DNA Quality

Abstract: The selection of spermatozoa without DNA fragmentation and chromosomal diseases prior to assisted reproductive techniques helps to optimize the outcome of the treatment; in particular, sperm selection prior to in vitro fertilization (IVF) or intracytoplasmic sperm injection (ICSI) is crucial. In fact, although ICSI has been successfully and safely applied worldwide for almost 20 years, at the present time we have no real knowledge regarding the hypothetical long-term side effects on ICSI adults, given the incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 176 publications
0
15
0
Order By: Relevance
“…Although the number of events in some studies is relatively small and the study characteristics are variable, tests for DNA damage and selection of undamaged sperm should be considered as part of the diagnostic and treatment pathways for those with recurrent pregnancy failure. Selecting ICSI sperm by maturation markers such as hyaluronic acid or other zona pellucida receptors, and/or by novel noninvasive imaging techniques, could help to prevent fertilization by DNA-damaged sperm (69). Further research is required into the mechanisms responsible for and preventing DNA damage, including antioxidant therapy.…”
Section: Discussionmentioning
confidence: 98%
“…Although the number of events in some studies is relatively small and the study characteristics are variable, tests for DNA damage and selection of undamaged sperm should be considered as part of the diagnostic and treatment pathways for those with recurrent pregnancy failure. Selecting ICSI sperm by maturation markers such as hyaluronic acid or other zona pellucida receptors, and/or by novel noninvasive imaging techniques, could help to prevent fertilization by DNA-damaged sperm (69). Further research is required into the mechanisms responsible for and preventing DNA damage, including antioxidant therapy.…”
Section: Discussionmentioning
confidence: 98%
“…This is further important in the ICSI technique, as the single spermatozoon injected, which is only selected based on morphology and motility, may carry a high risk of having damaged DNA (Lopes et al, 1998;Parmegiani et al, 2014).…”
Section: Variablesmentioning
confidence: 99%
“… 17 Whether DGC increases or decreases sDF is currently unclear. Indeed, although several studies have indicated that DGC improves the yield of DNA-intact spermatozoa, 18 others have reported no change or even a worsening of DNA quality in DGC-selected spermatozoa. 19 23 In addition, and most importantly, whether an eventual effect of DGC procedure on DNA damage impacts pregnancy achievement by ART is presently unknown.…”
Section: Introductionmentioning
confidence: 99%